2005
DOI: 10.1111/j.1348-0421.2005.tb03755.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Real‐Time PCR for Quantitative Detection of Clostridium botulinum Type A Toxin Gene in Food

Abstract: The TaqMan real‐time PCR method for the quantitative detection of C. botulinum type A was developed based on sequence‐specific hybridization probes. The validity of this assay was verified by using 10 genera of 20 strains, including reference strains of C. botulinum types A, B, C, D, E and F. The detection limit of this assay was evaluated on C. botulinum type A, using a 10‐fold dilution series of DNA and spores. The DNA and spores were detected up to level of 0.1 ng/ml and 102 spores/ml, respectively. Spore s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
0
19
0
4
Order By: Relevance
“…This allows the whole analysis to be finished within a working day. However, the speed is achieved at the cost of sensitivity; no fewer than 100 spores are detected (223). As the natural contamination levels of C. botulinum in food, clinical, and environmental samples may be 10 to 1,000 spores/kg, it is obvious that enrichment steps are needed for successful detection.…”
Section: Molecular Detection Of Clostridium Botulinummentioning
confidence: 99%
“…This allows the whole analysis to be finished within a working day. However, the speed is achieved at the cost of sensitivity; no fewer than 100 spores are detected (223). As the natural contamination levels of C. botulinum in food, clinical, and environmental samples may be 10 to 1,000 spores/kg, it is obvious that enrichment steps are needed for successful detection.…”
Section: Molecular Detection Of Clostridium Botulinummentioning
confidence: 99%
“…Realtime PCR detection of neurotoxin genes was also reported 23)ῌ27) . Among these studies, quantitation for type A was reported by Yoon et al 23) and quantitation for type E was described by Kimura et al 27) Real-time quantitative PCR has a number of advantages as compared to conventional assays for the detection or quantification of foodborne bacteria. The results are shown as fluorescence intensity, and the absence of electrophoresis eliminated the need for reopening of the reaction tubes, thus limiting the risk of carry-over contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported the detection and/or quantification of C. botulinum neurotoxin genes for type A 23) , for types A, B, and E 24), 25) , for types A and B 26) , and for type E 27) . Other real-time PCR approaches, which involve quantification of RNA expression, were reported for types A and E 28) , for type B 29), 30) , and for type D 31) .…”
Section: Introductionmentioning
confidence: 99%
“…By far, the most commonly employed methods are PCR-based techniques (Mullis et al 1986;Saiki et al 1988), many of which aim at detecting bont genes by conventional or quantitative amplification reactions (Szabo et al 1992(Szabo et al , 1993Franciosa et al 1994Franciosa et al , 1996Fach et al 1995Fach et al , 2009Takeshi et al 1996;Aranda et al 1997;Braconnier et al 2001;Kimura et al 2001;Craven et al 2002;Popoff and Walker 2003;Akbulut et al 2004;Takeda et al 2005;Yoon et al 2005;Lindström and Korkeala 2006;Artin et al 2007;Fenicia et al 2007;Heffron and Poxton 2007;Prévot et al 2007;Sánchez-Hernández et al 2008;Sakuma et al 2009;Hill et al 2010;Lindberg et al 2010;Takahashi et al 2010). Since conventional PCR is difficult to quantify and requires a post-PCR step to visualize and to verify the PCR product, many modern approaches use quantitative PCR (qPCR) formats.…”
Section: Dna-based Detection Of Bont-producing Bacteriamentioning
confidence: 99%